New graduate nurses as knowledge brokers in general practice in New Zealand: a constructivist grounded theory. (3rd May 2013) - Hoare, Karen J.; Mills, Jane; Francis, Karen
Abstract: Practice nursing in New Zealand is not well described in the literature. One survey illustrated that most of the New Zealand practice nurses sampled did not know of the country's two premier evidence‐based health websites. A recent review compared general practice in the UK, New Zealand and Australia and found that whereas there had been significant developments in empowering the practice nurse workforce to run nurse‐led clinics in the UK, New Zealand and Australia lagged behind. The aim of this reported constructivist grounded theory study was to investigate practice nurses' use of information. Conducted in Auckland, New Zealand, data were collected through ethnographic techniques in one general practice between September 2009 and January 2010 to enhance theoretical sensitivity to the area of information use. Subsequently, six experienced practice nurses (one twice after moving jobs) and five new graduate nurses from five different general practices were interviewed, using open‐ended questions, between January 2010 and August 2011. Concurrent data collection and analysis occurred throughout the study period. The use of memos, the constant comparative method, data categorisation and finally, data abstraction resulted in the final theory of reciprocal role modelling . Experienced practice nurses role modelled clinical skills to new graduate nurses. Unexpectedly, new graduate nurses were unconscious experts at sourcing information and role modelled this skill to experienced practice nurses. Once this attribute was acknowledged by the experienced practice nurse, mutual learning occurred that enabled both groups of nurses to become better practitioners. Graduate nurses of the millennial generation were identified as a resource for experienced practice nurses who belong to the baby boomer generation and generation X.